2011
DOI: 10.1111/j.1464-410x.2011.10628.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with Gleason score 8–10 prostate cancer: relation to preoperative PSA level

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? High‐grade prostate cancers are associated with poor disease‐specific outcomes. A proportion of these tumours produce little PSA. This study demonstrates that among Gleason 8–10 prostate cancers, some of the worst survival outcomes are associated with the lowest PSA levels. OBJECTIVE To assess outcomes of patients with Gleason score 8–10 prostate cancer (CaP) with a low (≤2.5 ng/mL) vs higher preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
(44 reference statements)
2
37
0
1
Order By: Relevance
“…In a study of 354 patients with carcinoma prostate (Gleason score 8-10) by McGuire BB et al, 17.5% had PSA level<4ng/ml [17] . In a similar study by Thompson IM et al, 15.2% had PSA <4ng/ml, out of which 14.9% had a Gleason score of 7 or higher [6] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study of 354 patients with carcinoma prostate (Gleason score 8-10) by McGuire BB et al, 17.5% had PSA level<4ng/ml [17] . In a similar study by Thompson IM et al, 15.2% had PSA <4ng/ml, out of which 14.9% had a Gleason score of 7 or higher [6] .…”
Section: Discussionmentioning
confidence: 98%
“…This could result in these tumours being diagnosed at a later stage than tumours producing more PSA. Also, patients with high grade, low PSA tumours have poorer prognosis than those of higher PSA levels [17] . The mean value of S.PSA in Grade 1 Adenocarcinoma was 8ng/ml, in Grade 2 was 42.5ng/ml, in Grade 3 was 44.1ng/ml and in Grade 4 was 61.8ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the relationship between pretreatment PSA level and clinical outcomes, including recurrence and death, when serum PSA levels are ''normal'' ( [10][11][12]). A few have suggested that in certain situations the association may be inverse -that higher PSA can be associated with a better outcome ( [11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…A few have suggested that in certain situations the association may be inverse -that higher PSA can be associated with a better outcome ( [11,12]). This finding is consistent with the clinical observation that there is a subgroup of men with low serum PSA, yet biologically aggressive PC.…”
Section: Introductionmentioning
confidence: 99%